ARTIFICIAL INTELLIGENCE IN HEALTHCARE, A NEW FIELD OF BIOETHICS - TOURAINE, Pr. Jean-Louis (MEDECINE LEGALE DROIT MEDICAL, 2025)
The fast development of artificial intelligence in the health sector has already resulted in important progresses for the benefit of patients (diagnosis, treatment, surgical robot…) as well as public health and management of the health system. This evolution requires a profond ethical reflection and both rules and controls. The relationship of the doctor to his patient must not be altered but, on the contrary, amplified when this new tool is introduced in the care process. Identification of drawbacks and their prevention, risk of further inequalities between various populations need to be analysed, in the face of the numerous advantages of AI in the field of health cares.